The Effect of Cognitive Performance on Static Balance Index - Roostayi, Mohammad Mohsen; Kamandi, Samaneh; Jalili, Neda; Khosravi, Mobina (Journal of Clinical Physiotherapy Research, 2023)
Introduction: In simultaneous assignments, "attention" must be divided between assignments. Due to the competition in processor resources, the result of this action is the reduction of the performance efficiency, at least in one of the tasks. Research on the effect of cognitive task on balance is not conclusive, and the effect of cognitive task and types of tasks at the same time on balance is unknown. The aim of the study is to investigate the intervention effect of two cognitive and visual tasks on balance. Materials and Methods: In this semi-experimental study, 20 young girls performed the test in 4 modes, balance without intervention, balance with cognitive intervention, balance with visual intervention, and balance with both interventions, on the Biodex machine at instability level 4. Overall stability index was recorded as dependent variable. Results: The results of variance analysis of repeated measurements at the level of P<0.05 did not show a significant difference between static balances in different situations. Therefore, all research hypotheses were rejected. Conclusion: It seems that the lack of significant difference between the different positions is related to the lack of control of the participants’ cognitive capacity and the created cognitive load and its effect on the posture control mechanisms.